2020
DOI: 10.1371/journal.pntd.0008676
|View full text |Cite
|
Sign up to set email alerts
|

Cross-serotypically conserved epitope recommendations for a universal T cell-based dengue vaccine

Abstract: Dengue virus (DENV)-associated disease is a growing threat to public health across the globe. Co-circulating as four different serotypes, DENV poses a unique challenge for vaccine design as immunity to one serotype predisposes a person to severe and potentially lethal disease upon infection from other serotypes. Recent experimental studies suggest that an effective vaccine against DENV should elicit a strong T cell response against all serotypes, which could be achieved by directing T cell responses toward cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 80 publications
(173 reference statements)
0
16
0
Order By: Relevance
“…The dengue virus (DENV) is transferred into the bodies of mammals (humans) through the bite of female mosquitos known as Aedes Aegypti ( Simo et al 2019 ). The lifespan of the mosquito is brief but after the larvae has the potential of spreading the virus from 4 to 10 days ( Ahmed et al 2020 ). Our study concludes promising potential of biosynthesized NPs as an effective and affordable approach to control the Aedes Aegypti and thus of the dengue fever.…”
Section: Discussionmentioning
confidence: 99%
“…The dengue virus (DENV) is transferred into the bodies of mammals (humans) through the bite of female mosquitos known as Aedes Aegypti ( Simo et al 2019 ). The lifespan of the mosquito is brief but after the larvae has the potential of spreading the virus from 4 to 10 days ( Ahmed et al 2020 ). Our study concludes promising potential of biosynthesized NPs as an effective and affordable approach to control the Aedes Aegypti and thus of the dengue fever.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used SARS-CoV immunological data for prediction [ [1] , [2] , [3] , [4] ] are shown in bold font, while all other studies that used peptide-HLA binding prediction methods are in regular font. In silico studies [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ] were obtained from PubMed, while the remaining studies [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , ...…”
Section: In Silico Methods Used For Sars-cov-2 T Cell Epitopmentioning
confidence: 99%
“…Motivated by the high genetic similarity of SARS-CoV with SARS-CoV-2, multiple in silico studies [ [20] , [21] , [22] , [23] ] used the information of T cell epitopes available from previous SARS-CoV immunological studies to predict likely targets of SARS-CoV-2 T cell responses ( Table 1 ). This approach is well motivated, with cross-reactive T cell epitopes being reported previously for genetically similar viruses [ 27 ], including zika virus, dengue virus, and other flaviviruses [ [28] , [29] , [30] , [31] ]. Interestingly, this was also the basic idea behind the first successful vaccine against an infectious disease, developed by Jenner in 1796, which induced protective immunity against the smallpox virus through inoculation with a related cowpox virus.…”
Section: In Silico Methods Used For Sars-cov-2 T Cell Epitopmentioning
confidence: 99%
“…Starting with each SARS-CoV-2 peptide and predicted HLAs individually, we find considerable coverage of 55.32% for "LLLD*", while "VQID*" exhibits the lowest predicted coverage of 7.09% (Fig 6D). Similarly to a previous approach by Ahmedid et al 42 , we set out to predict the accumulated global population coverage of the set. We found that 8 peptides collectively produce >90% global coverage, while the entire set is predicted to elicit T cell responses in 92.93% of the global population (Fig 6E).…”
Section: Identification Of Shared and Private Immunogenic Sars-cov-2 Peptidesmentioning
confidence: 99%